2022
DOI: 10.3390/ijms23179701
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Physiological and Transcriptomic Analyses of Two Contrasting Pepper Genotypes under Salt Stress Reveal Complex Salt Tolerance Mechanisms in Seedlings

Abstract: As a glycophyte plant, pepper (Capsicum annuum L.) is widely cultivated worldwide, but its growth is susceptible to salinity damage, especially at the seedling stage. Here, we conducted a study to determine the physiological and transcriptional differences between two genotype seedlings (P300 and 323F3) with contrasting tolerance under salt stress. The P300 seedlings were more salt-tolerant and had higher K+ contents, higher antioxidase activities, higher compatible solutes, and lower Na+ contents in both thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Therefore, it is speculated that the old leaves of BS will fall off due to the accumulation of too much Na + under high NaCl conditions. The excess accumulation of Na + in plant cells will induce cytosolic K + efflux and then lead to an imbalance in cellular homeostasis [ 46 , 47 ]. In this study, the K + content in the leaves of the two hibiscus cultivars decreased with the increase in NaCl concentration, which is in contrast to that of intracellular Na + , implying that high NaCl concentration on the outside leads to an increase in Na + content in cells, which in turn causes cytosolic K + efflux in hibiscus leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is speculated that the old leaves of BS will fall off due to the accumulation of too much Na + under high NaCl conditions. The excess accumulation of Na + in plant cells will induce cytosolic K + efflux and then lead to an imbalance in cellular homeostasis [ 46 , 47 ]. In this study, the K + content in the leaves of the two hibiscus cultivars decreased with the increase in NaCl concentration, which is in contrast to that of intracellular Na + , implying that high NaCl concentration on the outside leads to an increase in Na + content in cells, which in turn causes cytosolic K + efflux in hibiscus leaves.…”
Section: Discussionmentioning
confidence: 99%
“…These results correlate with the improved performance of salinized plants showing an increased value in their shoot and in their stomatal density. It was demonstrated that a salt tolerant pepper genotype showed a much higher level of transcripts of CAT2, APX2 and other antioxidant genes in respect to susceptible genotype when subjected to salt stress (Zhang et al, 2022) suggesting a correlation between ROS scavenger and plant performance in salt stress conditions. Moreover, increased root biomass is often associated with an enhanced tolerance to salinity and drought stresses and in this context an important role is played by HSP90 (Yadav et al, 2021), also upregulated following plant treatments with speci c EFs.…”
Section: Gene Expressions Analysismentioning
confidence: 99%